Eternally vigilant : free speech in the modern era - Bollinger, Lee C., 1946-; Stone, Geoffrey R. (The University of Chicago Press, 2018)
While freedom of speech has been guaranteed us for centuries, the First Amendment as we know it today is largely a creation of the past eighty years. Eternally Vigilant brings together a group of distinguished legal scholars to reflect boldly on its past, its present shape, and what forms our understanding of it might take in the future. The result is a unique volume spanning the entire spectrum of First Amendment issues, from its philosophical underpinnings to specific issues like campaign regulation, obscenity, and the new media. "With group efforts, such as this collection of essays, it is almost inevitable that there will be a couple--and often several--duds among the bunch, or at least a dismaying repetition of ideas. Such is not the case here. . . . Whether one agrees with a given author or not (and it is possible to do both with any of the essays), each has something to add. Overall, Eternally Vigilant is a thoughtful and thought-provoking book, consistently intelligent and, at times, brilliant."--Richard J. Mollot, New York Law Journal Contributors: Lillian R. BeVier Vincent Blasi Lee C. Bollinger Stanley Fish Owen M. Fiss R. Kent Greenawalt Richard A. Posner Robert C. Post Frederick Schauer Geoffrey R. Stone David A. Strauss Cass R. Sunstein.
Previously issued in print: 2002.
Preface Dialogue Freedom of Speech and the Common-Law Constitution Free Speech and Good Character: From Milton to Brandeis to the Present "Clear and Present Danger" and Criminal Speech The Speech Market and the Legacy of Schenck Reconciling Theory and Doctrine in First Amendment Jurisprudence First Amendment Opportunism The Dance of Theory The Invisible Hand of the Marketplace of Ideas The Censorship of Television The Future of Free Speech Epilogue List of Contributors Index.
Keywords: Freedom of speech -- United States.; Liberté d'expression -- États-Unis.; LAW -- Constitutional.; LAW -- Public.; Freedom of speech; United States; civil rights, constitutional law, first amendment, us constitution, legal scholars, american government, governing, press, media, affirmative action, diversity, higher education, supreme court, case studies, john milton, brandeis, marketplace of ideas, free speech, freedoms, jurisprudence, opportunism, censorship, television, modern era, social issues.; Electronic books.